Migration, transfers and child labor - Ralitza Dimova; Gil S. Epstein; Ira N. Gang (Osteuropa-Institut Regensburg, 2011)
We examine agricultural child labor in the context of emigration, transfers, and the ability to hire outside labor. We start by developing a theoretical background based on Basu and Van, (1998), Basu, (1999) and Epstein and Kahana (2008) and show how hiring labor from outside the household and transfers to the household might induce a reduction in children's working hours. Analysis using Living Standards Measurement Survey (LSMS) data on the Kagera region in Tanzania lend support to the hypothesis that both emigration and remittances reduce child labor.
Keywords: D62; F22; I30; J13; J20; J24; O15; 330; child labor; emigration; transfers; Tanzania; Kinderarbeit; Landwirtschaft; Rücküberweisung (Migranten); Internationale Arbeitsmobilität; Schätzung; Tansania